Peningkatan Kinerja Dan Keberlangsungan Usaha UMKM Sektor Pedagang Kecil Pada Pasar Besar Kota Palangka Raya Melalui Peningkatan Literasi Keuangan - Rahman, Rahman; Alexandro, Rinto; Liling Lenlioni; Kharisma Nugraha Putra; Zola Ari Setyanto; Febry, Febry (FKIP, Universitas Palangka Raya, 2025)
Micro, small and medium enterprises (MSMEs) are one of the main driving factors that contribute significantly to the economic improvement of a region. Despite this, MSMEs have efforts to create jobs and have high quality labor absorption. MSMEs have the ability to drive stable, long-term, and sustainable economic growth as they are considered to be able to survive even under crisis conditions. The fact that they can be established with little capital or investment means that MSMEs can be considered to have the ability to grow and develop quickly. For this reason, one of the factors that influence MSMEs to continue to develop is an understanding of good financial management, namely through financial literacy. This financial literacy is very important to study because everyone who has a business must certainly be able to understand financial literacy well, because basically this financial literacy can affect the way a person thinks about financial conditions and affect strategic decision making in terms of finance and management